Justification of the choice of excipients during the development of the composition of "Pastinocard" tablets - N. А. Symonenko; O. S. Shpychak; O. S. Kukhtenko; Ye. A. Bezrukavyi; H. B. Yurieva (Zaporozhye State Medical University, 2023)
The aim of the work is to justify the choice of excipients as components for the cardioprotective medicine "Pastinocard" tablets based on the domestic raw material of cultivated parsnip herb thick extract (CPHTE). Materials and methods. Experimental test samples of mixtures of the plant substance of domestic origin CPHTE with groups of excipients, approved for medical use, were used as the object of research. Results. We conducted experimental research by a mathematical planning method called the Greek-Latin square. In this study, we investigated how 16 different auxiliary substances affected the pharmacotechnological properties of tableting masses and tablets made from PPTEG with cardioprotective properties. Our goal was to determine the optimal composition and manufacturing process for a medication, specifically "Pastinocard" tablets. We also developed project plans for manufacturing regulations and quality control methods, which we successfully tested in the industrial production setting at Pharmaceutical Company "Zdorovye", LTD in Kharkiv. Conclusions. The formulation for cardioprotective tablets, designated as "Pastinocard", has been both theoretically justified and experimentally developed by domestic CPHTE raw materials. These research findings have been instrumental in crafting the regulatory documentation for quality control and the production processes of the resulting tablet medication.